2017
DOI: 10.15405/epsbs.2017.12.40
|View full text |Cite
|
Sign up to set email alerts
|

Creative Storytelling In Childhood Is Related To Exam Performance At Age 16

Abstract: Creativity is only partly recognised in education. A recent meta-analysis estimated a correlation of r = 0.22 between creativity and educational achievement across many international student samples of all educational levels. In the meta-analysis, creativity was measured with a variety of measures, including divergent thinking and remote association tasks. The differences in the measures influenced the strength of the relationship between creativity and educational achievement. More research is needed to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…Assessment Technique (CAT) has been applied (Baer, Kaufman, & Gentile, 2004;Hennessey & Amabile, 1988;Toivainen et al, 2017). A recent pilot study assessed creativity in children's written stories on 10 dimensions using the CAT (Toivainen et al, 2017). An exploratory factor analysis on the 10 dimensions, revealed two independent factors, based on high factor loadings, which were labelled as Creative Expressiveness and Logic.…”
Section: Many Measures Of Creativity Have Been Proposed For Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessment Technique (CAT) has been applied (Baer, Kaufman, & Gentile, 2004;Hennessey & Amabile, 1988;Toivainen et al, 2017). A recent pilot study assessed creativity in children's written stories on 10 dimensions using the CAT (Toivainen et al, 2017). An exploratory factor analysis on the 10 dimensions, revealed two independent factors, based on high factor loadings, which were labelled as Creative Expressiveness and Logic.…”
Section: Many Measures Of Creativity Have Been Proposed For Childrenmentioning
confidence: 99%
“…Previous studies have reported associations between creativity and similarly defined factors (e.g. Barron, 1955;Hennessey & Amabile, 1988;Mumford, 2003;Toivainen et al, 2017).…”
Section: Many Measures Of Creativity Have Been Proposed For Childrenmentioning
confidence: 99%
See 3 more Smart Citations